Data Protection by Design in the E-Health Care Sector Theoretical and Applied Perspectives - Bincoletto, Giorgia (Luxemburger Juristische Studien - Luxembourg Legal Studies, 2021)
In the digital age, e-health technologies play a pivotal role in the processing of medical information. As personal health data represent sensitive information concerning a data subject, enhancing data protection and security of systems and practices has become a primary concern. This book explores how an e-health system could be developed and how data processing activities could be carried out to apply data protection principles and requirements from the design stage. There is currently a lack of clarity and knowledge on the topic among developers, data controllers and stakeholders. The research attempts to bridge the gap between the legal and technical disciplines on DPbD by providing a set of guidelines for the implementation of the principle in the e-health care sector.